Abstract 23 A First Insight into the Validity of Post-Thaw Cell Recovery, Viability, and Potency Over Time. (6th September 2022) - Liu, Lin; McDonald, Trish; Elwood, Ngaire
Abstract: Introduction: Testing of a thawed segment or representative sample of a cord blood unit (CBU) for cell recovery, viability, and potency forms part of pre-release testing. Not all CBUs that have had pre-release testing completed are shipped for transplant, due to postponed or cancelled shipment request, and are therefore kept in the inventory until they are searched again. In an effort to identify these CBUs for future expedited release, the World Marrow Donor Association (WMDA) initiated a project to flag them as "Ready to Ship" in the WMDA Search & Match Service. However, it is not known how long post-thaw results are valid before they must be repeated on another thaw. Such information can be beneficial not only for transplant centers to better assess CBU suitability but also for Cord Blood Banks (CBBs) to avoid unnecessarily exhausting their precious samples. Objective: This study aimed to provide a first insight into the validity of post-thaw results over various lengths of time. Methods: Nineteen CBUs, collected between 2003 and 2015 at the BMDI CBB and that had post-thaw testing performed twice, were analyzed for change in the total nucleated cell (TNC) recovery, total CD34 cell recovery, CD34 cell viability, and CFU-GM counts between two thaws. Results: The 19 CBUs were grouped into 4 groups based on their storage time between thaws. An average decrease in TNC recovery of 5.3% from first thaw to second thaw was observed for the entire dataset ( P = .015). Four CBUs with a greater than 10% decrease had a bag TNC greater than 25 × 10 8 . Individual CBU data is shown in Figure 1. No significant change between thaws was seen with total CD34 recovery ( P = .738) or CD34 viability ( n = 9 pairs, P = .354). A large variation in CFU-GM counts was observed between thaws. It is worth noting that all CBUs met CBB release criteria of >60% TNC recovery and that CD34 viabilities were above 70% (FACT requirement) in both thaws. Discussion: While results need to be confirmed on a larger dataset, our preliminary data shows very little change in post-thaw cell recovery and viability over various lengths of time (2 months-12 years), suggesting post-thaw results may be valid for longer than 10 years.